Kant and Zetetic Scepticism - Kubok, Dariusz (Ruch Filozoficzny, 2022)
This article examines Immanuel Kant’s criticism from the perspective of the preceding tradition of critical thought, with particular emphasis on Greek philosophy. Kant himself views criticism as a way to go beyond dogmatism and scepticism. On the other hand – as many researchers point out – Kant’s philosophy develops certain themes present in ancient scepticism. In the literature, there are numerous studies demonstrating Kant’s debt to the Pyrrhonian scepticism characteristic of Sextus Empiricus (ephecticism and epechism). In this article, I try to show that two different interpretations of scepticism can be formed on the basis of Sextus’ writings: zetetic scepticism and ephectic scepticism. The interpretation considers ἐποχή and ἰσοσθένεια as key ideas for scepticism and it is this latter option that is recognized in Kant’s thought by scholars, especially by Michael Forster. In my opinion, however, it is the first interpretation, not yet sufficiently recognized, that constitutes at least an equally strong complement to the first and may even be regarded as the proper source of Kant’s critical philosophy.